ANALISIS DAMPAK LIMBAH CAIR PADA PABRIK TAHU TERAHADAP PENCEMARAN LINGKUNGAN DI KECAMATAN TANJUNG MORAWA KAB. DELI SERDANG - Fakhreisya Muharrahmi; Meisya Aldani, Nisa Indriani, Abdurrozzaq Hasibuan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Waste can form as long as tofu processing is still running. Waste that is not disposed of properly can pollute the environment (Indah et al., 2014). This also occurs in the tofu manufacturing factory located in the Tanjung Morawa area, or more precisely Jalan Sultan Serdang, where tofu waste is available in solid and liquid forms. The froth that forms when washing soybeans is known as solid waste. The remaining pulp is usually called tofu dregs; However, when washing tofu, liquid waste is produced. The purpose of this study was to determine the impact of liquid waste in tofu factories on environmental pollution in Kec. Tanjung Morawa to clarify the entire scope of the problem. This study uses a qualitative description approach, which assists in providing information, facts, and data. The research technique used was by interviewing and documenting the tofu factory workers. According to a study of liquid waste at the tofu factory on Jalan Sultan Serdang, Tanjung Morawa District, it has positive and negative impacts. Tofu Solid Waste has a good impact because it can be sold to cattle breeders to be processed into animal feed. Of course this will increase the income of the owner of the Tofu Business, but the negative impact will be pollution of water sources. This is because the liquid waste from the tofu industry is discharged directly into large trees which then flow into the river. There is a possibility that an unpleasant odor will be produced if it is not processed properly and disease will occur in workers due to the incomplete PPE used